2017
DOI: 10.1177/1468797617708511
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising on-screen tourism destination development

Abstract: This paper integrates cultural theory and marketing strategy to examine the complex relationship between on-screen popular culture and tourism destination place-making. Its review of the literature results in the development of an inter-disciplinary conceptual framework (termed 'on-screen dollying') that provides a culturally-grounded and contextually-driven theorisation of the means by which on-screen popular culture place-making can foster destination development. In developing the conceptual framework, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 93 publications
1
27
0
12
Order By: Relevance
“…Representations of Turkish culture and of women's issues appearing in Turkish soap operas play a significant role in making Istanbul an attractive destination. More precisely, “from a dramatological perspective, on‐screen productions can be analyzed as texts conveying messages that project and/or explain the culture of a destination and its attractive characteristics to outsiders” (Lundberg et al. 6).…”
Section: Resultsmentioning
confidence: 99%
“…Representations of Turkish culture and of women's issues appearing in Turkish soap operas play a significant role in making Istanbul an attractive destination. More precisely, “from a dramatological perspective, on‐screen productions can be analyzed as texts conveying messages that project and/or explain the culture of a destination and its attractive characteristics to outsiders” (Lundberg et al. 6).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been suggested that what unites the decidedly local and small‐scale efforts in Cong and its environs to capitalize on film tourism and the considerably more large‐scale activities of Tourism Ireland is a shared emphasis on cinematic authenticity and fan participation. Clearly, the screen fictions in both cases differ, not least because The Quiet Man was set in Ireland, albeit in a fictional town, while The Force Awakens was set in a purely fictional world and was merely filmed on location in Ireland (see Lundberg et al.). Equally, while the entirety of the former was set in Ireland, the latter (and the Last Jedi , which followed it) was only partly filmed in Ireland, although the narrative structure might lead one to reasonably conclude that Ahch‐To is the most important place in the film.…”
Section: Peripherality As Promotional Blueprintmentioning
confidence: 99%
“…No two films or TV shows are alike, which provides the portrayed destinations with a clear unique sales position” (93). Media tourism is a “dynamic place‐making phenomenon” (Lundberg et al. 94), but many studies of screen tourism conceptualize this placemaking as a struggle between an established real place and a fictional imaginary.…”
Section: Cultural Politics Of Placementioning
confidence: 99%